Book Reviews (The Australian journal of anthropology, 2002)
Book reviewed in this article: Ildiko Beller-Hann and Chris Hann. Turkish Region: State, Market and Social Identities on the East Black Sea Coast. Santa Fe Lewis Roberts Binford. Constructing Frames of Reference: An Analytical Method for Archaeological Theory Building Using Ethnographic and Environmental Data Sets. Anne Chambers and Keith Stanley Chambers. Unity of Heart: Culture and Change in a Polynesian Atoll Society. Marcus Colchester and Christian Erni (eds). Indigenous Peoples and Protected Areas in South and Southeast Asia. Michelle Ruth Gamburd. The Kitchen Spoon's Handle: Transnationalism and Sri Lanka's Migrant Housemaids. David N. Gellner and Eric Hirsch (eds.). Inside Organizations: Anthropologists at Work. Geoffrey Gray (ed.). Jane C. Goodale, Ruth Fink, Jeremy Beckett, L. R. Hiatt, and J. A. Barnes. Before It's Too Late: Anthropological Reflections, 1950–1970. John N. Gray. At Home in the Hills: Sense of Place in the Scottish Borders. Kees Grijns and Peter J. M. Nas (eds). Jakarta-Batavia: Socio-cultural Essays. Stephen Gudeman. The Anthropology of the Economy: Community, Market, Culture. Sarah Lamb. White Saris and Sweet Mangoes: Aging, Gender and Body in North India. Michael O'Hanlon and Robert Welsch (eds). Hunting the Gatherers: Ethnographic Collectors, Agents and Agency in Melanesia, 1870s–1930s. Sherry B. Ortner. Life and Death on Mt. Everest: Sherpas and Himalayan Mountaineering. Judy and Tashi Tenzing. Tenzing and the Sherpas of Everest. Adrian Peace. A World of Fine Difference: The Social Architecture of a Modern Irish Village. George W. Stocking, Jr. Delimiting Anthropology: Occasional Inquiries and Reflections. Colin Tatz. Aboriginal Suicide Is Different: A Portrait Of Life and Self-Destruction. Roger Tol, Kees van Dijk, and Greg Acciaioli (eds). Authority and Enterprise among the Peoples of South Sulawesi Penny Van Esterik. Materializing Thailand.